Health system strengthening: Integration of breast cancer care for improved outcomes. (29th April 2020) - Horton, Susan; Camacho Rodriguez, Rolando; Anderson, Benjamin O.; Aung, Soe; Awuah, Baffour; Delgado Pebé, Lucia; Duggan, Catherine; Dvaladze, Allison; Kumar, Somesh; Murillo, Raúl; Mra, Rai; Rositch, Anne F.; et al.
Abstract : The adoption of the goal of universal health coverage and the growing burden of cancer in low‐ and middle‐income countries makes it important to consider how to provide cancer care. Specific interventions can strengthen health systems while providing cancer care within a resource‐stratified perspective (similar to the World Health Organization–tiered approach). Four specific topics are discussed: essential medicines/essential diagnostics lists; national cancer plans; provision of affordable essential public services (either at no cost to users or through national health insurance); and finally, how a nascent breast cancer program can build on existing programs. A case study of Zambia (a country with a core level of resources for cancer care, using the Breast Health Global Initiative typology) shows how a breast cancer program was built on a cervical cancer program, which in turn had evolved from the HIV/AIDS program. A case study of Brazil (which has enhanced resources for cancer care) describes how access to breast cancer care evolved as universal health coverage expanded. A case study of Uruguay shows how breast cancer outcomes improved as the country shifted from a largely private system to a single‐payer national health insurance system in the transition to becoming a country with maximal resources for cancer care. The final case study describes an exciting initiative, the City Cancer Challenge, and how that may lead to improved cancer services. Abstract : Providing care for breast cancer can benefit, and benefit from, health system strengthening efforts. This consensus manuscript examines the role of essential medicine/essential diagnostics lists, national cancer plans, the financing of a specific set of public services, and how breast cancer programs can build on various other programs, along with case studies from different countries.